2020
DOI: 10.1093/braincomms/fcaa081
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and elderly MRI-based hippocampus and amygdala volume: a 7-year follow-up study

Abstract: Oxytocin is deeply involved in human relations. In recent years, it is becoming clear that oxytocin is also involved in social cognition and social behavior. Oxytocin receptors are also thought to be present in the hippocampus and amygdala, and the relationship between oxytocin and the structure and function of the hippocampus and amygdala has been reported. However, few studies have investigated oxytocin and its relationship to hippocampus and amygdala volume in elderly people. The aim of this study is to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 94 publications
(107 reference statements)
2
54
0
Order By: Relevance
“…This was a longitudinal study conducted in Kurokawa-cho, Imari, Saga Prefecture, Japan, among people aged 65 years and above, as reported previously ( Nabeta et al, 2014 ; Matsushima et al, 2015 ; Imamura et al, 2017 ; Orihashi et al, 2020 ). Kurokawa-cho is in northwestern Saga Prefecture and is a rural town somewhat cut-off from urban areas.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…This was a longitudinal study conducted in Kurokawa-cho, Imari, Saga Prefecture, Japan, among people aged 65 years and above, as reported previously ( Nabeta et al, 2014 ; Matsushima et al, 2015 ; Imamura et al, 2017 ; Orihashi et al, 2020 ). Kurokawa-cho is in northwestern Saga Prefecture and is a rural town somewhat cut-off from urban areas.…”
Section: Methodsmentioning
confidence: 90%
“…Brain MRI processing and analysis were conducted using voxel-based morphometry (VBM) ( Ashburner and Friston, 2000 ) implemented with Statistical Parametric Mapping (SPM12; Wellcome Department of Cognitive Neurology, London, United Kingdom) in MATLAB R2016a (MathWorks, Natick, MA, United States). We used the same methodology described in a previous study ( Orihashi et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies using similar methods, we observed that serum oxytocin levels in the elderly were positively correlated with the future hippocampus and amygdala volumes [15]. The hippocampus and amygdala are closely related to cognitive function.…”
Section: Discussionmentioning
confidence: 66%
“…This was a longitudinal study. The survey was conducted in Kurokawa -cho, Imari, Saga Prefecture, Japan, among people aged 65 years and above, as reported previously [12][13][14][15]. Kurokawa-cho is in northwestern Saga Prefecture and is a rural town somewhat cutoff from urban areas.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation